Autoestima y rendimiento académico del área de matemática en estudiantes del quinto ciclo de educación primaria de la Institución Educativa N° 61023 Rosa Licenia Vela, Nauta 2023 - Ramirez Lavi, Gilda Lety (2024)
The purpose of this study was to know the relationship between the academic performance of students in mathematics in the fifth cycle of primary education and their level of self-esteem. This is a non-experimental, quantitative, cross-sectional, descriptive-correlational study. The population was made up of eighty-five students in the fifth cycle of primary school, and the sample was census-based. A registration form was used as an instrument and documentary analysis was used as a technique for the Academic Performance variable, while the Coopersmith questionnaire was used for the Self-esteem variable. Statistical graphs were used to analyze the averages and percentages of the data tables. The students in the sample have low self-esteem and their academic performance is still developing, according to the data. The following conclusions were the most pertinent: By using a non-parametric test of free Chi-square distribution with two degrees of freedom and a significance level of 0.01 in fifth cycle students of the Primary Educational Institution No. 61023- Nauta, The study hypothesis was confirmed that there is a statistically significant relationship between self-esteem and academic performance in the area of mathematics.